2020
DOI: 10.1007/s00432-020-03445-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lung cancer and renin–angiotensin blockade: a concise review

Abstract: Purpose The blockade of the renin–angiotensin–aldosterone system (RAAS) by angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) is one of the most common treatments for hypertension, heart failure and renal diseases. However, concerns have been raised about a possible link between RAAS-blockers and an increased risk of cancer, particularly of lung cancer. This narrative review aims to give a critical appraisal of current evidence and to help physicians understand potential l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Therefore, understanding molecular mechanisms and developing an effective therapeutic approach for lung cancer are of paramount importance. Interestingly, the renin-angiotensin system plays an important role in lung tumor progression or metastasis [ 4 ]. It has been shown that the low expression of angiotensin-converting enzyme 2 (ACE2) is associated with tumor grade in lung cancer and that upregulation of ACE2 suppresses the progression of non-small cell lung cancer (NSCLC) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding molecular mechanisms and developing an effective therapeutic approach for lung cancer are of paramount importance. Interestingly, the renin-angiotensin system plays an important role in lung tumor progression or metastasis [ 4 ]. It has been shown that the low expression of angiotensin-converting enzyme 2 (ACE2) is associated with tumor grade in lung cancer and that upregulation of ACE2 suppresses the progression of non-small cell lung cancer (NSCLC) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The differences in risk associations between ACEi and ARBs have been controversial. 46 , 47 In a post-hoc analysis of a RCT, 48 ACEi was associated with increased risk of lung cancer. However, in a nationwide retrospective cohort analysis of 70,000 community-dwelling adults in the United States, 49 ARBs were associated with reduced risk of lung cancer (HR=0.74, 0.67-0.83).…”
Section: Discussionmentioning
confidence: 99%
“…ARB has been reported to be associated with inhibition of AT1R, which activates cell migration, cell proliferation, inflammation, and angiogenesis in lung cancer. 21 On the other hand, ACEIs are known to induce lung accumulation of bradykinin and substance P, which promote tumour proliferation and angiogenesis). 22 Breast cancer is necessary to clarify cancer-specific biological plausibility.…”
Section: Discussionmentioning
confidence: 99%